Toward bridging the gap between theory and empirical reality - Saunders, Stephen Graham (The South African Journal of economics, 2008)
Introductory (i.e. first year) undergraduate learners often perceive economics to be remote from reality and overly theoretical, leading to a lack of motivation and enthusiasm to study economics. A general survey of curriculum practice reveals that lecture materials and the pedagogic approach to teaching introductory economics often do not place the current “mainstream” economic theory into its philosophical context. The result being that the learners are unable to bridge the gap between economic theory and empirical reality. This paper argues that research into effective teaching and learning should focus not only on learner characteristics but also on curriculum content and its philosophical underpinnings, in order to research why students hold these negative perceptions. The paper recommends that introductory undergraduate teaching needs to engage in a critical examination, with the learner, of the philosophical underpinnings of “mainstream” economic theory and to introduce debates about the implications of these into the curriculum. This would create exciting new opportunities for teachers and learners to explore the connections between economic theory and social science in general and should come a long way in changing the negative perceptions of introductory undergraduate economics.